2015
DOI: 10.5897/ijmms2014.1108
|View full text |Cite
|
Sign up to set email alerts
|

Health care providers satisfaction with the clinical laboratory service of Nekemte Referral Hospital, Western Ethiopia

Abstract: The objective of this study was to assess health care providers' satisfaction with the service provided by the clinical laboratory personnel at Nekemte Referral Hospital, Western Ethiopia to determine the level of satisfaction of health care providers on clinical laboratory services. A cross sectional study was conducted from March to April, 2014 at Nekemte Referral Hospital. The data was collected from 105 randomly selected health professionals. The collected data was analysed using Statistical Package for So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
4
5
0
Order By: Relevance
“…The current study also showed that 71% of physicians' perceived quality of laboratory service was inconsistent in all working shifts. This finding was consistent with reports from Tanzania, Alexanderia, Gondar University Hospital, Nekemte referral hospital, and selected hospitals in east Ethiopia region [21,22,14,16,18].…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…The current study also showed that 71% of physicians' perceived quality of laboratory service was inconsistent in all working shifts. This finding was consistent with reports from Tanzania, Alexanderia, Gondar University Hospital, Nekemte referral hospital, and selected hospitals in east Ethiopia region [21,22,14,16,18].…”
Section: Plos Onesupporting
confidence: 92%
“…Turnaround time is one of the most noticeable signs of laboratory service and is used by many physicians to judge the quality of the laboratory. Previous studies from Tanzania, Alexanderia, Korea, Gondar University Hospital, Nekemte referral hospital and selected hospitals in east Ethiopia region, and College of American Pathologists reported similar finding that physicians were not satisfied with timely notification of panic results and provision of urgent services in a timely fashion [21,22,15,14,16,18,5]. The issue of ineffective communication between physicians and laboratory staff on patient care remains unresolved, therefore, there is a need of active communication between laboratory and physicians in any case of patient care activities.…”
Section: Plos Onementioning
confidence: 81%
See 2 more Smart Citations
“…Many aspects of laboratory services could be investigated from the clinician's perspective, such as the availability of ordered tests, courier services, availability of a helpful user guidebook, courtesy and respect, laboratory report format, turnaround time (TAT) of results, noti cation of critical results, and reliability of results [5,6]. Previous studies in Ethiopia have shown that physicians were most dissatis ed with the provision of timely results, advisory services and noti cation of panic values [14][15][16][17], including the behavioural manners of providers [14,18]. However, many argue the validity of user satisfaction as a measure of quality, particularly technical aspects, as users could be more sensitive to behavioural aspects [18,19].…”
Section: Introductionmentioning
confidence: 99%